Taxing Human Capital Efficiently – The Double Dividend of Taxing Nonqualified Labour More Heavily Than Qualified Labour - Wolfram F. Richter (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Assuming isoelastic returns to education and an endogenous supply of qualified and nonqualified labour, it is shown to be second-best efficient not to distort the choice of education. Furthermore, taxation should set incentives so that qualified labour is substituted for nonqualified labour. As a result, it is efficient to tax labour income regressively with respect to qualification and to tax the monetary cost of education at a level that restores efficiency in education. Atax on capital income alleviates the distortion that progressive taxation of labour income exerts on human-capital investment.
Keywords: H21; I28; J24; 330; Endogenous choice of education and labour; efficient taxation of human and nonhuman capital; double-dividend hypothesis; Bildungsverhalten; Lohnsteuer; Optimale Besteuerung; Qualifikation; Doppelte Dividende; Theorie